2022
DOI: 10.3389/fphar.2022.991421
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation promotes repair following spinal cord injury by restoring neuronal mitochondrial bioenergetics via AMPK/PGC-1α/TFAM pathway

Abstract: Background: Insufficient neuronal mitochondrial bioenergetics supply occurs after spinal cord injury (SCI), leading to neuronal apoptosis and impaired motor function. Previous reports have shown that photobiomodulation (PBM) could reduce neuronal apoptosis and promote functional recovery, but the underlying mechanism remains unclear. Therefore, we aimed to investigate whether PBM improved prognosis by promoting neuronal mitochondrial bioenergetics after SCI.Methods: Sprague Dawley rats were randomly divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Chronic inflammatory response and oxidative stress in skeletal muscle after SCI may be the mechanisms leading to atrophy (9,(67)(68)(69). At present, the known factors and related proteins involved in skeletal muscle atrophy include: tumor necrosis factor-alpha (TNF-α) and its receptor (70)(71)(72), human tumor necrosis factor-related weak apoptosis-inducing factor (TWEAK) and its receptor (56, 67, 73), interleukin-1β (IL-1β) (72,74), interleukin-6 (IL-6) and its receptor (75,76), growth factor (IGF-1) (77, 78), human dystrophin (Fbox-1, also known as Atrogin-1) (79, 80), musclespecific RING finger protein 1 (MuRF1) (79,80), peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) (20,58,81), fibroblast growth factor-inducible receptor 14 (Fn14) (73), reactive oxygen species (ROS) (20,68,82) and others. The discovery of these skeletal dystrophins has provided a deeper understanding of skeletal muscle atrophy at the molecular level and suggest the possibility of intervening via corresponding signaling pathways and factors to delay the atrophy process or promote skeletal muscle regeneration.…”
Section: Cytokines Associated With Skeletal Muscle Atrophy After Scimentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic inflammatory response and oxidative stress in skeletal muscle after SCI may be the mechanisms leading to atrophy (9,(67)(68)(69). At present, the known factors and related proteins involved in skeletal muscle atrophy include: tumor necrosis factor-alpha (TNF-α) and its receptor (70)(71)(72), human tumor necrosis factor-related weak apoptosis-inducing factor (TWEAK) and its receptor (56, 67, 73), interleukin-1β (IL-1β) (72,74), interleukin-6 (IL-6) and its receptor (75,76), growth factor (IGF-1) (77, 78), human dystrophin (Fbox-1, also known as Atrogin-1) (79, 80), musclespecific RING finger protein 1 (MuRF1) (79,80), peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) (20,58,81), fibroblast growth factor-inducible receptor 14 (Fn14) (73), reactive oxygen species (ROS) (20,68,82) and others. The discovery of these skeletal dystrophins has provided a deeper understanding of skeletal muscle atrophy at the molecular level and suggest the possibility of intervening via corresponding signaling pathways and factors to delay the atrophy process or promote skeletal muscle regeneration.…”
Section: Cytokines Associated With Skeletal Muscle Atrophy After Scimentioning
confidence: 99%
“…Oxidative stress-mediated skeletal muscle atrophy after spinal cord injury Peroxisome proliferator-activated receptor-γ coactivator (PGC)α PGC-1α is a regulator of mitochondrial bioenergetics and abundantly expressed in skeletal muscle, and plays an essential role in skeletal muscle repair after SCI via transformation of fasttwitch to slow-twitch muscle fibers (77,81,110,111). It can induce mitochondrial biogenesis, and by up-regulating nuclear respiratory factors 1,2 (Nrf1, 2) and mitochondrial transcription factors expressed against oxidative stress in skeletal muscle and spinal cord (81,112) it can increase myoglobin activity and promote energy metabolism in skeletal muscle. After SCI, PGC-1α expression decreases (110), and expression of myosin heavy chain protein also decreases accordingly (31).…”
Section: Interleukin /mentioning
confidence: 99%
“…In addition, PBM could regulate reactive oxygen species (ROS) production and activate a variety of transcription factors thus it has been used to treat SCI, ischemic stroke, traumatic brain injury, Alzheimer's disease and so on 26–29 . However, mitochondrial dysfunction that occurs after SCI limits the therapeutic effect of PBM 30 …”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29] However, mitochondrial dysfunction that occurs after SCI limits the therapeutic effect of PBM. 30 To address the problems mentioned above, we first studied embedded laser fiber-mediated PBM combined with platelet-derived mitochondrial transplantation in the treatment of SCI. Our results indicated that combined treatment was better than that of a single treatment in terms of motor function recovery, tissue repair, and inhibition of neuronal apoptosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation